2012
DOI: 10.2740/jisdh.22.308
|View full text |Cite
|
Sign up to set email alerts
|

A present state of attitudes to cooking in university students, and changes on the attitudes and the skills through a cooking class

Abstract: We conducted a survey on daily food habits including the frequency of cooking for university students in Kumamoto. There were three sign Ficaut results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…A significant positive association between the frequencies of breakfast and self-cooked meal intake was confirmed. A previous study of Japanese subjects revealed a positive relationship between the frequencies of cooking and breakfast intake among university students who lived alone [ 28 ], which is consistent with the result of this study. In Japan, breakfast is generally consumed at home.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A significant positive association between the frequencies of breakfast and self-cooked meal intake was confirmed. A previous study of Japanese subjects revealed a positive relationship between the frequencies of cooking and breakfast intake among university students who lived alone [ 28 ], which is consistent with the result of this study. In Japan, breakfast is generally consumed at home.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in recent years, numerous studies have considered the association of cooking at home or eating out with healthy dietary intake in the United Kingdom and United States [ 23 , 24 , 25 , 26 , 27 ]. In Japan, studies have also considered the association of cooking at home or eating out with healthy dietary intake [ 28 , 29 , 30 ]. However, the results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a nationwide survey on Japanese food culture [ 13 ], the percentage of adults who cook “almost every day” decreased by 0.8% (42.7–41.9%) from 2015 to 2019. Possible reasons for such a decline in home cooking in Japanese households are limited time [ 14 , 15 ], time consumption [ 15 ], and lower cooking skills [ 16 , 17 , 18 ]. In contrast, possible factors contributing to the high cooking frequency were confidence in cooking skills and positive perceptions of cooking (i.e., cooking is fun and not troublesome) [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons for such a decline in home cooking in Japanese households are limited time [ 14 , 15 ], time consumption [ 15 ], and lower cooking skills [ 16 , 17 , 18 ]. In contrast, possible factors contributing to the high cooking frequency were confidence in cooking skills and positive perceptions of cooking (i.e., cooking is fun and not troublesome) [ 14 , 18 , 19 ]. Therefore, it is possible that the increased time at home enabled people to overcome some potential barriers to cooking since the additional time at home could be dedicated to enjoying cooking.…”
Section: Introductionmentioning
confidence: 99%